Stereotactic Biopsy in The Diagnosis of Small Brain Lesion - Das, Sukriti; Bhuiyan, Md Sharif; Ghosh, Dipankar; Rashid, Md Mamunur (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Stereotactic neurosurgery involves mapping the brain in a three-dimensional coordinate system. With the help of MRI and CT scans and 3D computer workstations, neurosurgeons are able to accurately target any area of the brain especially deep seated and brain stem. Objectives: Stereotactic brain biopsy is a minimally invasive procedure that uses this technology to obtain samples of brain tissue for diagnostic purpose of multiple brain disorder where start to any medication was impossible or no response to any medical management for long term. Materials and Methods: Twenty-five patients underwent stereotactic biopsy of brain lesions using“KOMAI” Stereotactic frame system and were enrolled. Results: Of the 25 cases, positive tissue biopsy was found in 20 cases. In 5 patients, biopsy showed gliotic brain tissue or normal brain tissue. There was no post-operative new deficits or mortality seen. Conclusion: Stereotaxy is minimally invasive procedure having no complication. So, before starting any medication blindly stereotactic tissue diagnosis can help a lot in many medical and surgical diseases. J Bangladesh Coll Phys Surg 2021; 39(1): 24-35